INNOVATIVE PROCESS FOR HIGHER-ORDER THINKING SKILL DEVELOPMENT IN DIGITAL CLASSROOM MANAGEMENT - Sirikanna, Jarmon; Phewngam, Sawitree; Utawan, Sombat; Klaitong, Pakpum; Taweepong, Piyapong (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were to study the combination of high-level thinking skills of learners from doing. Classroom activities according to the teaching plan process developed for use in digital learning management. Including interviews on the teaching process of high thinking skills of the faculty in all 8 subject categories. The tools used for data collection were 1) in-depth interviews, 2) observation forms, and 3) small group meetings. with document data analysis And the analysis of data from in-depth interviews was used to separate the main issues according to the structure of questions and small group meetings. The results showed that Innovative process to develop high thinking skills in digital learning management. It requires development in multiple dimensions to integrate higher-level thinking. by integrating the development of problem-solving skills development of analytical thinking skills Most of the activities are in the form of answering questions on the worksheets. which found a problem that organizing activities in the form of answering questions on the worksheet could not be organized continuously Therefore, the development of analytical thinking skills can only be effective for some children. Developing creative and positive thinking skills There are many forms of digital learning management. Learners enjoy learning in various ways according to the learning process. by using the learning theory creative with intelligence (Constructionism) Higher thinking skills in digital learning management should be promoted to be consistent with the context of the subject group. to make the learners integrate their thinking skills until finally becoming a higher level of thinking.